A High-Sensitivity and Low-Power Theranostic Nanosystem for Cell SERS Imaging and Selectively Photothermal Therapy Using Anti-EGFR-Conjugated Reduced Graphene Oxide/Mesoporous Silica/AuNPs Nanosheets - Chen, Yu-Wei; Liu, Ting-Yu; Chen, Po-Jung; Chang, Po-Hsueh; Chen, San-Yuan (Small (Weinheim an der Bergstrasse, Germany), 2016)
A high‐sensitivity and low‐power theranostic nanosystem that combines with synergistic photothermal therapy and surface‐enhanced Raman scattering (SERS) mapping is constructed by mesoporous silica self‐assembly on the reduced graphene oxide (rGO) nanosheets with nanogap‐aligned gold nanoparticles (AuNPs) encapsulated and arranged inside the nanochannels of the mesoporous silica layer. Rhodamine 6G (R6G) as a Raman reporter is then encapsulated into the nanochannels and anti‐epidermal growth factor receptor (EGFR) is conjugated on the nanocomposite surface, defined as anti‐EGFR‐PEG‐rGO@CPSS‐Au‐R6G, where PEG is polyethylene glycol and CPSS is carbon porous silica nanosheets. SERS spectra results show that rGO@CPSS‐Au‐R6G enhances 5 × 106 magnification of the Raman signals and thus can be applied in the noninvasive cell tracking. Furthermore, it displays high sensitivity (detection limits: 10−8m R6G solution) due to the “hot spots” effects by the arrangements of AuNPs in the nanochannels of mesoporous silica. The highly selective targeting of overexpressing EGFR lung cancer cells (A549) is observed in the anti‐EGFR‐PEG‐rGO@CPSS‐Au‐R6G, in contrast to normal cells (MRC‐5). High photothermal therapy efficiency with a low power density (0.5 W cm−2) of near‐infrared laser can be achieved because of the synergistic effect by conjugated AuNPs and rGO nanosheets. These results demonstrate that the anti‐EGFR‐PEG‐rGO@CPSS‐Au‐R6G is an excellent new theranostic nanosystem with cell targeting, cell tracking, and photothermal therapy capabilities. By integrating targeting antibody (anti‐epidermal growth factor receptor), hot‐spots between arrayed gold nanoparticles and surface‐enhanced Raman scattering mapping image, a controllable porous silica/carbon nanostructure is developed. Supported on a reduced graphene oxide substrate to achieve real‐time diagnosis with synergistic photothermal effects, on‐demand eradication of tumor cells in vitro is enabled.